Geochemical investigations of the Dunaszekcső loess-paleosoil sequence, Se Transdanubia, Hungary - Hum László (University of Szeged, Department of Mineralogy, Geochemistry and Petrology Szeged, 1998)
The paper discusses the relation between paleoclimate and geochemical characteristics of the Ioess-paleosol sequence of Dunaszekcso, Hungary. Geochemical properties of the sediments reflect the intensity of weathering and pedogenesis, thus five sediment types could be distinguished upon this basis. The weakly weathered loess formed under cold and arid climate, while the weathered loess accumulated during milder, more humid periods. The strongly weathered loess, overlying paleosols, shows intermediate character between loess and paleosol; its geochemical analysis indicates more intense weathering than in loess, but not intensive enough for soil formation. The Mende Upper and Basaharc Double paleosols were produced by strong pedogenesis, while the Basaharc Lower paleosol underwent the most advanced weathering and pedogenesis. Analyses of the geochemical character of different stratigraphic horizons allowed the reconstruction of paleoclimatic trends.
Keywords: Természettudományok; Föld- és kapcsolódó környezettudományok